Uma janela aberta para a leitura de mundo: o desenho de crianças de 9/10 anos a partir de intervenções pedagógicas - Bonci, Estela Maria Oliveira (2013)
Children through the language of the drawing can say whatever they think and at the same time can say anything. While drawing, children would be attached to aesthetic or culturally pre-established standards? Does the act of drawing in children occur free from interference, which simply they draw and give wings to your imagination? To answer these questions it was realized actions with 9/10 years old children in interdisciplinary projects involving the meeting between the cultural heritage of the city in the Parque Buenos Aires with its sculptures, and a long project in which previously actions prepared the children to live experiences near to the works of art that would be seen, without the kids knew earlier, in the exhibition Coleção, Ciência e Arte in the Centro Universitário Maria Antonia/USP (CEUMA). After contact with the exhibition, portfolios and other artistic productions were produced by children. The voices and drawings produced by children during the search showed us more than just marks on paper, points, lines or curves. In the analysis of the records and the children's drawings, with some observations also made visual observations through pictures, is that the wealth of productions can be unveiled and expanded. Developing, encouraging and monitoring the production of drawings we seek to understand how children represent their perceptions. Through the drawings of the children we rediscover the world supposedly known, if we know how to read their processes and productions and listen to them before, during and after their poetic actions.